1996
DOI: 10.1007/bf01979243
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of some diuretic agents

Abstract: Thermogravimetry-derivative thermogravimetry and differential scanning calorimetry were used to study the thermal behaviour of furosemide, hydrechlorothiazide, spironolaetone, and amiloride hydroehloride. The results revealed the extents of their thermal stability and also permitted interpretations concerning their thermal decompositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…TGA was used to analyse the thermal degradation temperature of both polymers and APIs. HCTZ, was previously reported to be thermally stable over a wide range of temperatures (Valladao et al, 1996) (stable up to at least 301 °C). This was verified in our studies, while RAM was shown to thermally degrade just above its melting point (at 123 °C) (Supplemental Figure S 1).…”
Section: Physiochemical Characterizationmentioning
confidence: 99%
“…TGA was used to analyse the thermal degradation temperature of both polymers and APIs. HCTZ, was previously reported to be thermally stable over a wide range of temperatures (Valladao et al, 1996) (stable up to at least 301 °C). This was verified in our studies, while RAM was shown to thermally degrade just above its melting point (at 123 °C) (Supplemental Figure S 1).…”
Section: Physiochemical Characterizationmentioning
confidence: 99%
“…Wendlandt and Collins 2 used DTA and TG thermal analysis techniques as aids in the characterization and identification of commercial non-preescription analgesics. Other investigations of the use of thermal analysis techniques for the study of drug substances and for applications in routine pharmaceutical analysis and in the pharmaceutical industry have also been described [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . No reference has been found on the application of TG and DSC in the study of trimethoprim, sulfamethoxazole, ampicillim, tetracycline hydrochloride, rifampim and association of sulfamethoxazole with trimethoprim.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that this mass loss corresponds to one of the three furosemide degradation steps. 48 For all APIs, no water loss was observed in the usual range (room temperature to 100 ºC), 32 which can be explained by the low TGA sensitivity.…”
Section: Thermogravimetric Analysismentioning
confidence: 90%